What's it all about? - Baggini, Julian (Oxford University Press, 2005)
What is the meaning of life? It is a question that has intrigued the great philosophers--and has been hilariously lampooned by Monty Python. Indeed, the whole idea strikes many of us as vaguely pompous, a little absurd. Is there one profound and mysterious meaning to life, a single ultimate purpose behind human existence? ...